A pea (Pisum sativum L.) seed albumin extract prevents colonic DSS induced dysbiosis in mice. (August 2017) - Aranda-Olmedo, Isabel; Ruiz, Raquel; Peinado, M. Jesús; Rubio, Luis A.
Highlights: The intestinal microbiota plays a relevant role in ABD pathogenesis. PSE is a pea ( Pisum sativum ) albumin protein extract. PSE pretreatment induced a recovery in colon length in DSS treated mice. PSE restored bacterial counts and composition to values in healthy mice. PSE partially prevented colonic microbiota alterations induced by DSS in mice. Abstract: This study investigates the effects of a pea ( Pisum sativum ) seed albumin extract (PSE) on the colonic microbiota in a model of experimental dextran sodium sulfate (DSS)-induced colitis in mice. Male C57BL/6J mice were assigned to three groups: one non-colitic and two colitic. Colitis was induced by incorporating DSS (3.5%) in the drinking water for four days, after which DSS was removed. The pre-treated group received orally PSE (15 g/kg·day) starting two weeks before colitis induction, and was maintained for nine days after. Mice pre-treated with PSE showed a recovery in colon length compared with non-treated DSS group. Both RT-qPCR and pyrosequencing analysis showed that DSS induced significant modifications in the microbiota composition of colonic contents and tissue. In conclusion, PSE modulated colonic microbiota in a model of experimental dextran sodium sulfate (DSS)-induced colitis in mice, and prevented colonic DSS induced dysbiosis in mice.